2020
DOI: 10.1021/acsanm.0c02274
|View full text |Cite
|
Sign up to set email alerts
|

Cs4PbBr6/CsPbBr3 Nanocomposites for All-Inorganic Electroluminescent Perovskite Light-Emitting Diodes

Abstract: In this study, the facile synthesis and electroluminescent perovskite light-emitting diodes (PeLEDs) of highly luminescent Cs 4 PbBr 6 /CsPbBr 3 nanocomposite has been demonstrated. With the addition of proper antisolvents, the nanocomposite with a production yield of >90% and quantum yield of >85% was readily derived from the transformation of CsPbBr 3 powder. The obtained high quantum yield of the green nanocomposite originated from the fluorescent CsPbBr 3 nanocrystals embedded in the Cs 4 PbBr 6 matrix, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 37 publications
0
22
1
Order By: Relevance
“…Such strong absorptions are attributed to the 1 S 0 → 3 P 1 transition of Pb 2+ centres. 37 On the other hand, the sharp absorption cutoff of transparent Cs 4 PbBr 6 occurs around 357 nm, which is obviously different from that of colored Cs 4 PbBr 6 as sharp absorption cutoffs occur around 361 and 554 nm in colored Cs 4 PbBr 6 SCs, which are deemed as the absorption edges. The first cutoff is deemed as the intrinsic absorption edge of pure Cs 4 PbBr 6 , which exhibits a red shift compared with other reports, 32,38 suggesting stronger absorption ability of our Cs 4 PbBr 6 SC.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Such strong absorptions are attributed to the 1 S 0 → 3 P 1 transition of Pb 2+ centres. 37 On the other hand, the sharp absorption cutoff of transparent Cs 4 PbBr 6 occurs around 357 nm, which is obviously different from that of colored Cs 4 PbBr 6 as sharp absorption cutoffs occur around 361 and 554 nm in colored Cs 4 PbBr 6 SCs, which are deemed as the absorption edges. The first cutoff is deemed as the intrinsic absorption edge of pure Cs 4 PbBr 6 , which exhibits a red shift compared with other reports, 32,38 suggesting stronger absorption ability of our Cs 4 PbBr 6 SC.…”
Section: Resultsmentioning
confidence: 98%
“…The introduction of Cl ions into SC leads to an absorption peak blue shift to 300 nm. Such strong absorptions are attributed to the 1 S 0 → 3 P 1 transition of Pb 2+ centres …”
Section: Resultsmentioning
confidence: 98%
“…In spite of the lack of understanding of the origin of the emission, the high solid-state PLQY and improved photostability of the 0D perovskites make them the most promising candidates for LED applications in the perovskite family. Several recent studies demonstrated that the inclusion of 0D perovskites in 3D perovskite films led to significant PL efficiency enhancement and higher current efficiency and external quantum efficiency in LEDs compared to the pure 3D devices. , However, in all of these cases, the 0D component (thin film) was non-emissive and acted only as a matrix/encapsulation layer to passivate the 3D surface. It was proposed that the 0D component can provide either dielectric confinement to the 3D part, enhancing its oscillator strength and absorption cross-section, or type-I confinement that enforces radiative recombination of the 3D core, or can enhance the emission by energy transfer from 0D to 3D .…”
Section: Optoelectronic Properties Of Low-dimensional Perovskitesmentioning
confidence: 99%
“…Motivated by their promising applications in optoelectronics, synthesis techniques of organic-inorganic hybrid and all-inorganic lead halide perovskites (AILHPs) in forms of powder and nanocrystals (NCs) with improved characteristics have gained remarkable developments in the last decade [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Despite those astonishing breakthroughs, e.g., the ultrahigh power conversion efficiency in solar cells and theoretically high external quantum efficiency in perovskite light-emitting diodes (PeLEDs) [ 2 , 3 ], the transition of halide perovskite devices from the laboratory into commercial products has been greatly hindered by their poor stabilities and phase transition/deformation tendencies [ 9 , 10 ]. Actually, three-dimensional (3D) AILHPs (CsPbX 3 ) show higher thermal decomposition stability for the inorganic nature when compared to their hybrid counterpart [ 10 ].…”
Section: Introductionmentioning
confidence: 99%